Context-aware mobile computing affordances of space, social awareness, and social influence - Gay, Geri (Morgan & Claypool Publishers, 2009)
The integration of ubiquitous mobile computing resources into physical spaces can potentially affect the development, maintenance, and transformation of communities and social interactions and relations within a particular context or location. Ubiquitous mobile computing allows users to engage in activities in diverse physical locations, to access resources specific to the location, and to communicate directly or indirectly with others. Mobile technologies can potentially enhance social interactions and users' experiences, extend both social and informational resources available in context, and greatly alter the nature and quality of our interactions. Activities using mobile devices in context generate complex systems of interactions, and the benefits of ubiquity and mobility can be easily lost if that complexity is not appreciated and understood. This monograph attempts to address issues of using and designing location-based computing systems and the use of these tools to enhance social awareness, navigate in spaces, extend interactions, and influence others
Keywords: Context-aware computing; Mobile computing; COMPUTERS / Hardware / Personal Computers / Macintosh; COMPUTERS / Hardware / Personal Computers / PCs; Electronic books